Assessment of Knowledge and Attitude of Health Workers About Dengue Fever at Al-Hodeidah Governorate - Mohammed M Al-Jabri; Adel M Al Jawfi (Sudan Journal of Medical Sciences)
Dengue fever (DF) is a viral disease transmitted by mosquitoes and is emerging as a serious global health problem. However, there is still a lack of knowledge regarding the disease. The aim of the study: To assess the knowledge and attitude of health workers about dengue fever in Al-Hodeidah governorate. Subjects and methods: Descriptive research design was used in the study with convenient sampling. The current study included 337 participants. Results: The study revealed that 53% of health workers had a fair knowledge level about dengue fever and 78.65% of them had a positive attitude about dengue fever. Conclusion: The study concluded that about half of health workers had fair knowledge about dengue fever. While about three-quarters of them had a positive attitude about dengue fever. Recommendations: According to the current study, educational programs for nurses and midwives on dengue fever management and prevention should be organized